1992
DOI: 10.1113/jphysiol.1992.sp018998
|View full text |Cite
|
Sign up to set email alerts
|

On the mechanism of action of picrotoxin on GABA receptor channels in dissociated sympathetic neurones of the rat.

Abstract: SUMMARY1. The mechanism of action of picrotoxin on GABA receptor channels in rat sympathetic neurones has been investigated with whole-cell clamp. In addition, the action of picrotoxin on single GABA channels has been examined in outside-out membrane patches from these cells.2. Picrotoxin, at concentrations which dramatically reduced the amplitude of whole-cell GABA currents, did not alter the spectral time constants or single-channel conductance estimated by analysis of GABA-activated current noise. This was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
170
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(184 citation statements)
references
References 40 publications
(43 reference statements)
12
170
2
Order By: Relevance
“…However, single channel analysis has shown that picrotoxin lacks the flickery effect that is typical of a classical channel blocker (12). In addition, picrotoxin inhibition is voltage-independent in these channels (3,12,13). Furthermore, other reports have demonstrated little or no usefacilitated block by picrotoxin in glycine and GABA C receptors, respectively (13,21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, single channel analysis has shown that picrotoxin lacks the flickery effect that is typical of a classical channel blocker (12). In addition, picrotoxin inhibition is voltage-independent in these channels (3,12,13). Furthermore, other reports have demonstrated little or no usefacilitated block by picrotoxin in glycine and GABA C receptors, respectively (13,21).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the fact that the onset of picrotoxin block is facilitated in the presence of the agonist in GABA A and glutamate-gated Cl Ϫ channels, it has been suggested that picrotoxin acts as an open channel blocker (3,5). However, single channel analysis has shown that picrotoxin lacks the flickery effect that is typical of a classical channel blocker (12). In addition, picrotoxin inhibition is voltage-independent in these channels (3,12,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Propofol and picrotoxin bind to GABA A receptors. Picrotoxin reduces GABA A receptor currents (38), whereas propofol increases GABA A receptor currents (16). Activation of p130cas is also regulated in a system without ion channels (46).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we concluded that nicotine is mainly a noncompetitive L-AChR antagonist, possibly acting through allosteric inhibition. Such a mechanism has been proposed for picrotoxin at GABA A receptors (36), and for some AChR noncompetitive antagonists such as the steroid promegestone that efficiently inhibits Torpedo AChRs most probably by increasing the fraction of desensitized receptors (37).…”
Section: ͼ97%mentioning
confidence: 99%